ANALISIS PENGARUH KUALITAS PELAYANAN, HARGATERHADAP LOYALITAS PELANGGANPADA JASA PENERBANGAN PT. SRIWIJAYA AIR AMBON - Sefnat Kristianto Tomasoa (Jurnal Riset Akuntansi dan Bisnis)
This study aims to determine the influence of service quality and price of customer loyaltyflightservice usersofPT.SriwijayaAirAmbon.The unitof analysis inthis study are allpassengerarrivalsanddeparturesin Ambon City.Samples taken using acidental purposive random sampling technique, ie passengers who encountered during the research and they've never been on a plane at least 2 times in the last 3 months.Datawere collected usingquestionnairedistributed tothe respondents, and then make tested the validity, reliability and multiple regression analysis with using SPSS. The results showed that the quality of service and price significant effect on customer loyalty. Service quality positive effect of 0.336 on customer loyalty PT. Sriwijaya Air Ambon. Price positive effect of 0.542 on customer loyalty PT. Sriwijaya Air Ambon. Seen from R square value of 0.68 which indicates that customer loyalty to the PT. Sriwijaya Air Ambon influenced by two variable that the quality of service and price by 68%, the remaining 32% customer loyalty PT. Sriwijaya Air Ambon influenced by other variables that have not been examined in this study.